Aprender a leer, leer para aprender - Roger Chartier (Centre de Recherches sur les Mondes Américains, 2010)
This article underlines, first, the persistence in the early modern European societies of forms of transmission of knowledge that do not presuppose reading, but oral speeches and images. It stresses, also the increasing importance of reading as an instrument for acquiring knowledge and its centrality in nineteenth century schools, when primary textbooks became a book of the book – and when some publishers proposed to popular readers encyclopedic collections. The increasing number of potential readers and the growing importance of reading practices led to the dissemination of manners of reading, multiplication of popular print, and the division of literary field between the “industrial literature” and “l’art pour l’art” addressed to the “happy few”. These two trends led also to the denunciation of the perils of (bad) readings, inherited from the eighteenth century, and the anxieties vis-a-vis the ambivalence of reading, that can be instrument for knowledge but also reader’s alienation. A reflection on the transformations imposed by the digital textuality on reading practices is the conclusion of this article.